Semiotika Michael Camille Riffaterre Studi Analisis Alquran Dalam Surat Al-Baqarah Ayat 223 - Fajrin, Siti Fatimah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2019)
In his book entitled Semiotic of Poetry, Riffaterre describes his theory called superreader. Initially, Riffaterre's semiotic theory was specifically used to analyze poetry, but in its development this theory could also be used to analyze other literary works. The literary meaning in Riffaterre's semiotics is in the form of (1) the unsustainability of poetic expressions (literary works) caused by displacing of meaning, distorting of meaning, and creating of meaning, (2) reading heuristic and hermeneutic or retroactive, (3) matrices, models, and variants, (4) hypograms or intertextual relationships. In Riffaterre's semiotics the conflict between meaning and significance plays a very important role. In the process of development, the meaning of the text of the Qur’an in this case QS. al-Baqarah verse 223 will give birth to various dynamics of meaning behind the verse to how the verse speaks with the verse maqashid coledors if elaborated the meaning of the verse using Riffaterre's semiotic theory. In connection with the Qur'an, the study of semiotics of the Qur'an begins by placing the Qur'an as a text. Text in the sense as a form of the use of signs (verses or signs) in the form of a combination or collection of a set of language and cultural signs that are combined in certain ways in order to produce certain meanings as well. This research is considered important because there are still few previous studies that discuss Riffaterre's semiotic theory using Alquran verses. The analysis of Alquran with the semiotic approach can be started by analyzing the building structure of the combination of the Alquran code that exists in Riffaterre's semiotic theory.